PEMBUATAN KOMIK KATA TUNJUK KORE (これ)、SORE (それ)、DAN ARE (あれ) UNTUK PEMBELAJARAN BAHASA JEPANG - Mardhiyah, Umayatun; Basri, Merri Silvia; Yohani, Adisthi Martha (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research aims to create a comic containing an explanation of thedemonstrative words kore, sore and are. The material for the demonstrative words kore,sore, are is one of the materials that must understand the concept of its use. Therefore, acomic was created that explains the material of the demonstrative words kore, sore, areby providing many examples of their use in everyday life. Comics are a visualcommunication medium that uses images arranged in a storyline to convey informationin an interesting and easy to understand way. This research method is the MultimediaDevelopment Life Cycle (MDLC) method which has 6 stages, namely conceptualizing,designing, collecting materials, manufacturing, testing and distribution. However, thisresearch is limited to the manufacturing stage. In this research, the stages of makingcomics are explained from start to finish. This research contributes to helping Japaneselanguage learners understand the grammar of the demonstrative words kore, sore, andare.Key Words: Learning media, Comics, The demonstrative words kore, sore, and are.